Corporate venture capital as a real option in the markets for technology. (9th October 2018) - Ceccagnoli, Marco; Higgins, Matthew J.; Kang, Hyunsung D.
Abstract : Research Summary : We apply real options (RO) theory to understand the role of corporate venture capital (CVC) investments and its relationship with internal R&D capabilities in supporting the acquisition of external technologies. We formulate hypotheses about key drivers of the option value of CVC and the decision to exercise the RO using a dyadic dataset of global pharmaceutical firms and their biotech partners. Our findings suggest that the option value of CVC is higher for investors with weaker scientific capabilities; engaging the markets for technology in distant technological fields; and, when their innovation pipeline is tilted toward the late‐stage development process. Finally, the licensing of high‐value technologies is the most likely form of option exercise when technological uncertainty is reduced post‐CVC. Managerial Summary : Despite the fact that one of the main goals of corporate venture capital (CVC) investments in high‐tech industries is to gain a window on future technologies, the relationship between CVC and other strategies used to acquire external technologies, such as licensing, has not been adequately explored. To address this gap, we formulate hypotheses about key drivers of the decision to make CVC investments as a wait‐and‐see strategy in the markets for technology (MFT) using a longitudinal dataset of global pharmaceutical firms and their biotech partners. We find that investors' scientific capabilities, technological domains, and research pipelines impact investors' decisions to make CVC investments prior to other MFT transactions. In our research setting, investors typically acquire high‐value technologies via licensing when technological uncertainty is reduced post‐CVC.